2007
DOI: 10.1161/01.hyp.0000255034.42285.58
|View full text |Cite
|
Sign up to set email alerts
|

Stress Management at the Worksite

Abstract: Abstract-Work stress may increase cardiovascular risk either indirectly, by inducing unhealthy life styles, or directly, by affecting the autonomic nervous system and arterial pressure. We hypothesized that, before any apparent sign of disease, work-related stress is already accompanied by alterations of RR variability profile and that a simple onsite stress management program based on cognitive restructuring and relaxation training could reduce the level of stress symptoms, revert stress-related autonomic ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(39 citation statements)
references
References 52 publications
1
37
0
1
Order By: Relevance
“…Interestingly, one study reported that employees with work-related stress showed significantly higher stress-related symptoms and higher LF component of HR than nonstressed workers and that these alterations were reverted by a stress management program. [52] The finding that the CBT group had improvement in HRV, but the combination treatment did not, is unexpected because the combined treatment group also experienced the same techniques of breathing retraining, progressive muscle relaxation, and cognitive restructuring. This outcome may be explained by the findings of Barlow et al, [3] where after treatment discontinuation, the combined imipramine and CBT group had the equivalent relapse rates as the imipramine only group, considerably higher than the CBT only and CBT plus placebo groups.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, one study reported that employees with work-related stress showed significantly higher stress-related symptoms and higher LF component of HR than nonstressed workers and that these alterations were reverted by a stress management program. [52] The finding that the CBT group had improvement in HRV, but the combination treatment did not, is unexpected because the combined treatment group also experienced the same techniques of breathing retraining, progressive muscle relaxation, and cognitive restructuring. This outcome may be explained by the findings of Barlow et al, [3] where after treatment discontinuation, the combined imipramine and CBT group had the equivalent relapse rates as the imipramine only group, considerably higher than the CBT only and CBT plus placebo groups.…”
Section: Discussionmentioning
confidence: 99%
“…We also disagree with calling exposure to work environment sources of stress as "lifestyle" stressors. We applaud the work praised by Milani and Lavie 3 and performed by Lucini et al 4 for furthering our understanding of autonomic dysregulation as a consequence of work stress and for testing the effectiveness of stress management. The relationship between environmentally measured job stressors and autonomic dysregulation has been documented, 5 and the use of heart rate variability as a measurement strategy for assessing individual response and cardiac disease risk is recommended.…”
Section: Stopping Stress At Its Origins: Addressing Working Conditionsmentioning
confidence: 90%
“…In this issue of Hypertension, Lucini et al 10 have elegantly demonstrated the relationship between work-related stress and autonomic dysregulation, specifically, oscillatory properties of RR variability that are thought to precede the development of frank hypertension. They describe a strong correlation between autonomic markers and stress perception scores and were capable of discriminating between affected workers and control subjects with a high degree of accuracy.…”
Section: -Charles Darwin Expression Of the Emotions In Man And Animalsmentioning
confidence: 99%
“…Lucini et al 10 have taken us in the direction where health care must move if we are to be successful in combating heart disease and other chronic conditions. Future work in prevention must include intervention aimed at the origin of disease.…”
Section: -Charles Darwin Expression Of the Emotions In Man And Animalsmentioning
confidence: 99%